Bashing is for the weak, WE factor

Algebra Level 5

In the following linear system:

a ( a + 2 ) 4 b ( b + 3 ) = 8 , 8 ( b 2 c ) ( b 2 + 2 b c + 4 c 2 ) 48 b c ( b 2 c ) = ( b + 2 c ) ( b 2 2 b c + 4 c 2 ) + 6 b c ( b + 2 c ) , a 4 + 81 c 4 = 12 a 3 c 54 a 2 c 2 + 108 a c 3 a(a+2)-4b(b+3)=8, \\ 8(b-2c)(b^2+2bc+4c^2)-48bc(b-2c)=(b+2c)(b^2-2bc+4c^2)+6bc(b+2c), \\ a^4+81c^4=12a^3c-54a^2c^2+108ac^3

there are two ordered triples ( u , v , w ) (u, v, w) and ( x , y , z ) (x, y, z) which satisfy the system. If u + v + w + x + y + z u+v+w+x+y+z can be represented as p q -\frac{p}{q} where p,q are positive co-prime integers, find p + q p+q .


The answer is 53.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Aayush Patni
Jan 28, 2015

What I did was I formed an equation in terms of c.
Let the two roots of the equation be w,z. Then I simply calculated the sum of w and z from the equation which comes out to be -22/45 . since we know that a=3c. For two values of c i.e. w and z, there will be two values of a- u and x. Therefore u+x= 3(w +z)
Similarly b= 6c . Therefore v+y= 6(w+z). Thus in the end the sum turns out to be 10(w+z)= -44/9. Thus p+q= 53

For the equation: a=3c , b= 6c Put the above values of a and b in the first equation.

Sorry for the bad presentation. I don't know how to type in Latex.

Trevor Arashiro
Jul 26, 2014

This is not a very in-depth solution.

The first equation can be factored into ( a + 1 ) 2 = ( 2 b + 3 ) 2 (a+1)^2=(2b+3)^2 . Which after square rooting becomes ( a + 1 ) = ± ( 2 b + 3 ) (a+1)=\pm(2b+3) . THE ± \pm IS VERY IMPORTANT. It is why we have 6 answers and not 3.

The second can be factored into 8 ( b 2 c ) 3 = ( b + 2 c ) 3 8(b-2c)^3=(b+2c)^3 .

The third can be factored into ( a 3 c ) 4 = 0 (a-3c)^4=0 .

Thus we get a = ( 2 b 4 , 2 b + 2 ) , b = 6 c , c = a 3 a=(-2b-4,2b+2), b=6c, c=\frac{a}{3} . The reason there are 2 solutions for each variable is that there are two a's, which means that both have to be plugged into the equation and two answers will result for each variable. Plugging these terms back into the original equation yields a = ( 4 5 , 2 3 ) , b = ( 8 5 , 4 3 ) , c = ( 4 15 , 2 9 ) a=(-\frac{4}{5},-\frac{2}{3}), b=(-\frac{8}{5},-\frac{4}{3}), c=(-\frac{4}{15},-\frac{2}{9}) .

Some simple arithmetic leads us to p q = 44 9 -\frac{p}{q}=-\frac{44}{9} . Thus p + q = 53 p+q=53

Does anyone know the LaTeX for the \=>

Trevor Arashiro - 6 years, 10 months ago

Log in to reply

The > with two lines coming out of it.

Trevor Arashiro - 6 years, 10 months ago

Log in to reply

Try \geq for \geq or \neq for \neq .

Calvin Lin Staff - 6 years, 10 months ago

Maybe you mean \implies . It's \implies.

Sean Ty - 6 years, 9 months ago

Nice solution Trevor

Aayush Patni - 6 years, 4 months ago

DO you expect us to factor the 2nd equation by hand? That's madness!

Pi Han Goh - 5 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...